Kinesthetic sense and awareness in wrestling: the structure, conditions and development of an "opponent's feeling" - Starosta, W. (International Journal of Wrestling Science, 2013)
The level of coordination abilities is of crucial importance in combat sports and martial arts. Its particular and very specific manifestation is the "opponent`s feeling" which exerts a considerable impact on the effectiveness of the fight. Despite the considerable importance of the "opponent`s feeling" this problem has been treated very marginally so far . The proof of the fact is the lack of verylittle number of publications [Blady et al., 1998; Starosta, 2003] and attempts to define the notion, to describe its structure and conditions of development. Therefore, the aim of the work was: 1. Define the term of "opponent`s feeling" in combat sports and martial arts competitors. 2. Specify components (structure) of "opponent`s feeling". 3. Define the conditions of high level of "opponent`s feeling". 4. Attempt to establish the conditions affecting the "opponent`s feeling" and methods of its development. 5. Look for reserves as far as the development of movement coordination, and focus particularly on its complex manifestation such as "opponent`s feeling", "mat feeling" etc. Material and method. Studies were conducted on 154 advanced athletes: wrestlers in classical style (n =50) and female and male wrestlers in freestyle (n=11+59=70), 20 kyokushinkai karatekas and 14 wrestling coaches. A particularly high level of advancement was recorded for wrestlers, who included former Olympic champions and medal winning athletes of the highest rank. Responses to 12 of them were then processed. The age of studied individuals was within 18-40 years, and the training period was 5-25 years. A questionnaire prepared by W. Starosta and containing 21 questions dealing with "opponent`s feeling" was research method. The questions concerned the "opponent`s feeling" among representatives of selected of combat sports and martial arts. Conclusions: 1. A complex manifestation of a high level of coordination abilities such as "opponent`s feeling" or "mat feeling" depend on a number of conditions: level of sport advancement, training experience, length of training period, part of training session, temperature of the surrounding, level of emotions etc. 2. The majority of the questioned observed in the themselves a higher level of "opponent`s feeling" during the start training period, rather than during preparatory period. 3. According to the surveyed (45%), the highest level of the "opponent`s feeling" occurred in the main/ core part of the training session, and the lowest in its further part (31%). 4. The symptoms of the high level of "opponent`s feeling" include: 4.1. The correct predicting of the opponent`s intentions; 4.2. Proper psychic attitude; 4.3. The certainty of the fight; 4.4. The improper of "opponent`s feeling" is the lack of these symptoms.